Keterampilan Proses Sains dan Sikap Ilmiah Calon Guru Biologi pada Mata Kuliah Zoologi Invertebrata - Dian Samitra; Muhammad Kristiawan (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2021)
This study aims to determine the profile of science process skills and scientific attitudes of prospective biology teachers in the Invertebrate Zoology course. The method used is descriptive to examine all students of the Biology Education Study Program in the second semester of the 2020/2021 academic year as research subjects. Process skills data were obtained from process skills observation sheets and scientific attitude data were obtained from questionnaires. The results showed that the science process skills of prospective biology teachers were 79.1% and scientific attitudes were 82.4%. In conclusion, the science process skills of Biology teacher candidates are classified as skilled with a good scientific attitude. Keywords: Biology Teacher Candidates, Science Process Skills, Scientific Attitude